KONTRIBUSI PENDAPATAN SEKTOR INFORMAL TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA PINABETENGAN UTARA KECAMATAN TOMPASO BARAT - Praise Iroth; O. Esry H. Laoh; Ribka M. Kumaat (Sam Ratulangi University, 2016)
The same opportunity to work in the informal sector to encourage farmers to make the decision to allocate the available workforce to be more efficient than that of bulk farm working hours also had a busy time and leisure time. The increased revenue adds the satisfaction level through the increase of consumption and leisure time. This research is to determine the contribution of informal sector income on household income Pinabetengan farmers in the Northern District of West Tompaso. This research was conducted in the village of North Pinabetengan, in June 2015 through December 2015. The data used are primary and secondary data. Primary data is data taken with direct interviews to farmers who have jobs in the informal economy. Secondary data is data taken from North Pinabetengan village office. The analysis has used in this study are presented in tabular form. The main commodities of farmers in the village are corn, beans, peanuts, rice and vegetables and spices. Farm income of farmers is the smallest Rp 600,000 and Rp 9,800,000 the greatest. The informal sectors has done such as motorcycle taxi, buggy, stalls, food stalls, craftsmen, traders, tailors, pitchman, garage, laundry worker. The lowest Income informal sector is Rp 500,000 and the highest is Rp 2,400,000. Results of the analysis showed that the contribution of the informal sector to household income of farmers amounted to 41.10 % with an average farm income in rural sub-district Tompaso Pinabetengan north west Rp . 1,600,833 / month , the average income of informal sector Rp . 1.177 million / month . So that the average total income of Rp . 2717833.Keyword: Contribution, Informal Sector, Income, North Pinabetengan Village, Minahasa